Hopefully I'm missing some very basic algebra for this question. In essence, I need to derive the following:

$$ \Omega=\Omega_{1}\frac{(1+z)}{1+\Omega_1{z}} $$ Now, I proceeded from the Friedmann equations as follows for a matter dominated Universe (and for $\Lambda=0$ and $k\neq{0}$): $$ \frac{H^{2}}{H_{0}}=\Omega_{m}a^{-3}+\Omega_{\kappa}a^{-2} $$ Knowing that $a=1/(1+z)$ I can re-arrange this to: $$ \frac{H^{2}}{H_{0}}=\Omega_m(1+z)(1+z)^2+\Omega_{\kappa}(1+z)^2 $$ $$ \frac{H^{2}}{H_{0}}=(\Omega_m+\Omega_mz)(1+z)^2+\Omega_{\kappa}(1+z)^2 $$ Introducing the fact that $1-\Omega_{m}=\Omega_{\kappa}$: $$ \frac{H^{2}}{H_{0}}=(\Omega_m+\Omega_{\kappa}+\Omega_mz)(1+z)^2=(1+\Omega_mz)(1+z)^2 $$ This is where I feel I am almost there but I've stumbled a little as to my next options. Any tips or advice would be brilliant!

  • $\begingroup$ Well for starters you need to introduce $\Omega_1$ and $\Omega$ in there with some other equation(s). $\endgroup$ – Chris Feb 9 '16 at 2:21
  • $\begingroup$ I assume by $\Omega_1$ you actually mean $\Omega_m$ (i.e. $\Omega_0$). You have derived how the Hubble parameter evolves. Now you need to use this to find how the density parameter evolves. THe density parameter is defined as $\Omega \equiv \rho/(3M_{\mathrm{pl}}^2H^2)$. $\endgroup$ – Philo Feb 9 '16 at 17:57

You almost have it. The last step is $$ \Omega = \frac{\rho}{\rho_\text{c}} = \frac{\rho_0\,a^{-3}}{\rho_\text{c,0}}\frac{\rho_\text{c,0}}{\rho_\text{c}} = \Omega_m\,(1+z)^3\frac{H_0^2}{H^2}, $$ where we used the critical density $$ \rho_\text{c} = \frac{3H^2}{8\pi G},\qquad \rho_\text{c,0} = \frac{3H_0^2}{8\pi G}. $$ The result follows immediately from what you already derived.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.